Dynamic Innovation in Outsourcing Theories, Cases and Practices (Technology, Work and Globalization, 2018)
This book is a guide for achieving innovation through outsourcing. Unpacking the various challenges faced by client firms and suppliers, the authors take the reader through the innovation lifecycle and devise a clear plan to achieve valuable results. Offering practical frameworks and tools to ensure informed decision-making at every stage, this book also includes collaborative structures and metrics to measure outcomes. Written by leading figures in the area of outsourcing, this book offers both the academic rigor and the hands-on experience based on dozens of cases that walk the reader from the very beginning of the outsourcing journey to the successful delivery of transformative innovations.